Efficacy and safety of sofosbuvir/ ledipasvir in treatment of patients with COVID-19; A randomized clinical trial - khalili, Hossein; Nourian, Anahid; Ahmadinejad, Zahra; Emadi Kouchak, Hamid; Jafari, Sirous; Dehghan Manshadi, Sayed Ali; Rasolinejad, Mehrnaz; Kebriaeezadeh, Abbas (Acta Biomedica Atenei Parmensis, 2020)
Background: There is no study regarding the use of SOF/LDP in treatment of COVID-19. Objectives: In this study, the efficacy and safety of SOF/LDP were assessed in treatment of patients with mild to moderate COVID-19. Methods: Among an open-label randomized clinical trial, 82 patients with mild to moderated COVID-19 were assigned to receive either SOF/LDP 400/100 mg daily plus the standard of care (SOF/LDP group, n=42) or the standard of care alone (control group, n=40) for 10 days. Time to clinical response, rate of clinical response, duration of hospital and ICU stay and 14-day mortality were assessed. Results: Clinical response occurred in 91.46% of patients. Although rates of clinical response were comparable between the groups but it occurred faster in the SOF/LDP group than the control group (2 vs. 4 days respectively, P= 0.02). Supportive cares were provided in the medical wards for most patients but 17.07% of patients were transferred to ICU during the hospitalization course. However, durations of hospital and ICU stay were comparable between the groups. 14-day mortality rate was 7.14% and 7.5% in the SOF/ LDP and control groups respectively. No adverse effects leading to drug discontinuation occurred. Gastrointestinal events (nausea, vomiting and diarrhea) were the most common side effects (15.85%). Conclusion: Added to the standard of care, SOF/LDP accelerated time to the clinical response. However, rate of clinical response, duration of hospital and ICU stay and 14-day mortality were not different. No significant adverse event was detected. More randomized clinical trials with larger sample sizes are needed to confirm the efficacy and safety of SOF/LDP in the treatment of COVID-19.